ChemInform Abstract: Interactions in Ionic Liquids Probed by in situ NMR Spectroscopy. Issue 47 (6th November 2014) - Giernoth, Ralf; Broehl, Andreas; Brehm, Martin; Lingscheid, Yves
Abstract Review: 42 refs.